The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1440-1827.2008.02295.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological characteristics of 21 Papua New Guinean children with high‐grade B‐cell lymphoma, which is frequently associated with EBV infection

Abstract: The aim of the present study was to confirm the histopathological features of aggressive B-cell lymphoma in Papua New Guinea (PNG)-an EBV endemic region. The immunophenotypic features and expression of EBV-encoded proteins and RNA in B-cell lymphomas were analyzed in 21 PNG children, and compared to the corresponding features of 17 Japanese children with Burkitt lymphoma (BL). Histological diagnosis of the lymphomas from the PNG children was BL in nine patients; atypical Burkitt/Burkitt-like variant of BL (BLL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Sporadic cases in nonimmunocompromised hosts were described in some Asian, African, and Latin America countries, where EBV infection is present in 70% to 80% of children by the age of 2 years. In Malaysia, 2 of 5 cases of DLBCL were EBV+ [8]; in Papua New Guinea, 1 of 4 cases was EBV+ [9]. Recently, it was reported that 10 of 25 cases of pediatric DLBCL occurring in Argentina were EBV+ [10].…”
Section: Introductionmentioning
confidence: 92%
“…Sporadic cases in nonimmunocompromised hosts were described in some Asian, African, and Latin America countries, where EBV infection is present in 70% to 80% of children by the age of 2 years. In Malaysia, 2 of 5 cases of DLBCL were EBV+ [8]; in Papua New Guinea, 1 of 4 cases was EBV+ [9]. Recently, it was reported that 10 of 25 cases of pediatric DLBCL occurring in Argentina were EBV+ [10].…”
Section: Introductionmentioning
confidence: 92%
“…Regarding EBV-host interactions, four different forms of virus latency have been recognized based on the rate of expression of EBV-encoded proteins and RNA. 35 Type 1, which is observed in Burkitt lymphoma, shows exclusive expression of EBV-encoded nuclear antigen 1 (small non-polyadenylated RNA (EBER) molecules and EBVencoded nuclear antigen 1 (EBNA-1)); type II, which is observed in Hodgkin's lymphoma, shows additional expression of LMP; type III, which is observed in lymphoproliferative disease (LPD) in immunocompromised patients, shows expression of all six EBNAs, all three LMPs and the two EBERs; type IV latency is less strictly defined and pertains to infectious mononucleosis and post-transplantation LPD. In the six cases of primary CNS EBV-positive diffuse large B-cell lymphomas of the elderly that we reported, we found that all cases examined expressed EBV EBNA1, EBNA2 and LMP1.…”
Section: Diffuse Large B-cell Lymphomas and Burkitt Lymphomasmentioning
confidence: 99%
“…In Israel, only 34% of BL cases have been shown to be EBER positive . In India and in Papua New Guinea, EBER was detected in 83‐91% of BL cases . Despite the similar climatic conditions and holoendemic malaria transmission in Malaysia, only 27% of BL cases harbored EBV; although nonsignificant, ethnic differences were observed, which suggest an ethnic predisposition .…”
Section: Discussion and Literature Reviewmentioning
confidence: 98%